The impact of visual vision training on learning the throwing skill in the badminton and some visual variables among the youth of AL-Kut sports Club - Kadhim, Haider Abdul; Hassan, Israa Fadel; Aziz, Hussein Fayek (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to identify the impact of visual vision training on learning the throwing skill in the badminton and some visual variables among the youth of AL-kut sports club The researcher used the experimental approach for its computability for the research application and its procedures, The research sample was selected in a deliberate manner among the juniors of the AL-Kut club in total (20) juniors divided into two groups each group contains 10 juniors one of them is the experimental and the other is the controlled group. The researcher applied the visual training program on the experimental group and the traditional method on the controlled group In light of the research goals and in terms of the sample size chosen and based on the results of the statistical calculations the researcher concluded the following: The visual training program has proven its effectiveness in improving junior’s visual abilities and improving the skill performance of the throwing skill in badminton. The researcher recommends establishing an optical measurements laboratory within each of the specialized clubs, the need for a visual specialist who evaluates and develops the visual abilities and functions of young players and determines the type of glasses and contact lenses in terms of efficiency and color to protect them, Further studies on the impact of visual exercises is needed on other sports using different samples.